STUDI KASUS PADA PASIEN DENGAN MASALAH KEPERAWATAN GANGGUAN PERSEPSI SENSORI: HALUSINASI PENDENGARAN DI POLI JIWA/PSIKIATRI RSUD Dr. R. SOSODORO DJATIKOESOMO BOJONEGORO: CASE STUDY IN A PATIENT WITH NURSING PROBLEMS OF SENSORY PERCEPTION DISORDERS: HEARING HALLUCINATIONS AT THE MENTAL POLY/PSYCHIATRY OF Dr. RSUD. R. SOSODORO DJATIKOESOMO BOJONEGORO - Rahmawati, Reni; Agung Susanti, Dwi; Muslima Isnanda Putri, Evita; Ari Afandi, Agus (LPPM STIKES Rajekwesi Bojonegoro, 2024)
ABSTRAK Gangguan persepsi sensori merupakan suatu keadaan yang terjadi dalam diri seseorang yang mengalami perubahan bentuk dan jumlah rangsangan yang datang dari luar sehingga mengakibatkan terjadinya gangguan persepsi sensori: halusinasi. Tujuan penulisan karya tulis ilmah ini Membandingkan asuhan keperawatan kasus pada 2 pasien dengan Masalah Keperawatan Gangguan Persepsi Sensori: Halusinasi Pendengaran di Poli Jiwa/Psikiatri RSUD Dr. R. Sosodoro Djatikoesomo Bojonegoro. Rancangan penelitian deskriptif dengan pendekatan studi kasus yang dilaksanakan pada bulan Mei tahun 2024 di Poli Jiwa/Psikiatri RSUD Dr. R. Sosodoro Djatikoesomo Bojonegoro. Partisipan dalam penelitian ini adalah 2 orang pasien Dengan Masalah Gangguan Persepsi Sensori: Halusinasi Pendengaran. Instrument yang digunakan adalah format asuhan keperawatan jiwa. Hasil pengkajian keperawatan pasien 1 dan pasien 2 didapatkan perbedaan yaitu dari isi , frekuensi halusinasi , dan diagnose prioritas. Sedangkan pada pasien 1 dan 2 di dapatkan persamaan yaitu dari faktor predisposisi terjanya halusinasi karena syndrome pasca trauma. Diagnose medis pada ke 2 pasien sama yaitu Gangguan Persepsi Sensori: Halusinasi Pendengaran. Evaluasi hasil SP (strategi pelaksanaan) pasien 1 dan 2 telah dilakukan sesuai teori. setelah diberikan asuhan keperawatan selama 5 hari. Kata Kunci: Gangguan Persepsi Sensori: Halusinasi Pendengaran. CASE STUDY IN A PATIENT WITH NURSING PROBLEMS OF SENSORY PERCEPTION DISORDERS: HEARING HALLUCINATIONS AT THE MENTAL POLY/PSYCHIATRY OF Dr. RSUD. R. SOSODORO DJATIKOESOMO BOJONEGORO ABSTRACT Sensory perception disorders are a condition that occurs in a person who experiences changes in the form and amount of stimulation coming from outside, resulting in sensory perception disorders: hallucinations. The purpose of writing this scientific paper is to compare case nursing care for 2 patients with nursing problems with sensory perception disorders: auditory hallucinations at the Psychiatric/Psychiatric Polyclinic at Dr. RSUD. R. Sosodoro Djatikoesomo Bojonegoro. Descriptive research design with a case study approach carried out in May 2024 at the Psychiatric/Psychiatric Polyclinic at Dr. RSUD. R. Sosodoro Djatikoesomo Bojonegoro. Participants in this study were 2 patients with sensory perception disorders: auditory hallucinations. The instrument used is the mental nursing care format. The results of the nursing assessment of patient 1 and patient 2 showed differences in terms of content, frequency of hallucinations, and priority diagnoses. Meanwhile, in patients 1 and 2, similarities were found, namely the predisposing factors for hallucinations due to post-traumatic syndrome. The medical diagnosis in both patients was the same, namely Sensory Perception Disorder: Auditory Hallucinations. Evaluation of SP results (implementation strategy) for patients 1 and 2 has been carried out according to theory. after being given nursing care for 5 days. Keywords: Sensory Perception Disorders: Auditory Hallucinations